Ways to increase the resistance of thermoelectric cooling modules to mechanical impacts - Razinkov, V.V.; Kuz, R.V.; Krechun, M.M. (Journal of Thermoelectricity, 2024)
The possibility of a significant increase in the resistance of thermoelectric modules to mechanical impacts is shown. The influence of the bandage anti-diffusion coating on the energy parameters of thermoelements has been determined. It has been shown that the use of thermoelements with an anti-diffusion bandage-type coating significantly increases the resistance of thermoelectric modules to mechanical impacts. Bibl. 14, Figs. 7.